2020
DOI: 10.1177/2380084420962778
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of US Adults Delaying Dental Care Due to the COVID-19 Pandemic

Abstract: Background: Coronavirus disease 2019 (COVID-19) has disrupted the delivery of health care services, including dental care. The objective of this study was to quantify and describe US adults who delayed dental care due to the COVID-19 pandemic. Methods: We analyzed cross-sectional responses collected from a nationally representative and long-running panel survey of US adults conducted in late May and early June 2020 (response rate = 70%). The survey included questions about dental care delayed due to the COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
65
4
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 9 publications
11
65
4
4
Order By: Relevance
“…The increased rate of infections may reflect sequelae that occurred due to suspended and deferred dental care or a pandemic-related omission in care seeking. A recent study, based on representative US survey data, reported that 46.7% of US adults delayed going to the dentist or receiving dental care owing to the COVID-19 pandemic [11]. The present retrospective study, likewise, suggests that the pandemic led a segment of the population to delay dental care in spite of an urgent treatment need.…”
Section: Discussionsupporting
confidence: 54%
“…The increased rate of infections may reflect sequelae that occurred due to suspended and deferred dental care or a pandemic-related omission in care seeking. A recent study, based on representative US survey data, reported that 46.7% of US adults delayed going to the dentist or receiving dental care owing to the COVID-19 pandemic [11]. The present retrospective study, likewise, suggests that the pandemic led a segment of the population to delay dental care in spite of an urgent treatment need.…”
Section: Discussionsupporting
confidence: 54%
“…16 Similarly, many allied health services had closed, limited their operations, or transitioned to telehealth. 17,18 Other studies have demonstrated dental care being delayed 19 and dental and allied health clinic closures during the COVID-19 pandemic. 20,21 This study demonstrated that access to medical providers, medication, and testing for non-HIV care largely continued with the vast majority able to access these services when required.…”
Section: Fig 3 High Proportions Of Plhiv Reported Feeling Sometimesmentioning
confidence: 99%
“…This disruption of the regular care structure put oncological patients with oral malignant lesions at increased risk, as screening examinations were suspended, and urgent symptomatic cases were prioritized for diagnostic intervention. Kranz et al conducted a survey within the US and found a delay in receiving dental care in nearly half of the population (46.7%) due to the COVID-19 pandemic [5]. Since oral precursor lesions and oral malignant lesions are mainly detected by dentists during routine screening, it is reasonable to assume that the nationwide lockdown and its restrictions on healthcare could have led to failures in the screening of high-risk patients and consequently to an increase in avoidable malignant lesions as well as a delayed diagnosis of oral tumors.…”
Section: Introductionmentioning
confidence: 99%